Co-immobilization of N-hydroxyphthalimide and cobaltous ions as a recyclable catalyst for selective aerobic oxidation of toluene to benzaldehyde. Issue 5 (October 2021) - Shi, Guojun; Lu, Qiuting; Xu, Jinyang; Wang, Jiajia; Ji, Lijun
Abstract: Selective aerobic oxidation of toluene to benzaldehyde has gained vast attentions due to its characteristics in environmental friendliness, atomic economy and a waiver of chlorine contamination. The separation, recovery and reuse of homogeneous catalysts will, however, be tricky. In this work, cobalt ions were immobilized by coprecipitation followed by a special washing, and the prepared cobalt-containing intermediate exhibited excellent textural properties and an exclusively low chemical state. 3-(Glycidoxypropyl) trimethoxysilicane (GPTMS) was used as a linking molecule to anchor N-hydroxyphthalimide (NHPI) onto the intermediate by C–O–N and Si–O–Si bonds, respectively, and a reliable covalent combination of NHPI was confirmed by the decomposition temperature and chemical states of N element in the co-immobilized NHPI/Co catalyst. The synthesized NHPI-GPTMS-CS catalyst exhibited a toluene conversion of 42.5% and a selectivity to benzaldehyde of 52.6% in hexafluoropropan-2-ol, which is much higher than the reactivity of toluene observed on the catalyst combination of commercial silica anchored NHPI (NHPI-GPTMS-SiO2 ) and homogeneous cobaltous ions, testifying an accessibility and a better synergy between N-oxyl radicals and cobaltous ions co-immobilized. There was no appreciable leaching of cobalt species and anchored NHPI observed for the co-immobilized catalyst and its activity for toluene oxidation was well remained, indicating an excellent reusable capability. It was observed that benzaldehyde is converted into benzoic acid, but benzyl alcohol into benzaldehyde and toluene via oxidation and disproportionation, respectively, over the synthesized co-immobilized catalyst. Toluene oxidation is suggested to proceed via a free radical mode and the produced water is one of the quenching agents. Graphical Abstract: ga1 Highlights: NHPI and cobaltous ions were co-immobilized on SiO2 to catalyze toluene oxidation. The co-immobilized NHPI/Co(II) exhibited well in toluene oxidation to benzaldehyde. The co-immobilized catalyst showed excellent reusability.